2016
DOI: 10.1111/jmft.12176
|View full text |Cite
|
Sign up to set email alerts
|

Most and Least Meaningful Learning Experiences in Marriage and Family Therapy Education

Abstract: Marriage and family therapy educators increasingly emphasize training competencies. What we know less about is what makes family therapy education meaningful to marriage and family therapy (MFT) graduate students and what does not. In this study, through an Internet survey, we explored the most and least meaningful learning experiences of 68 MFT graduate students and recent graduates of Commission on Accreditation for Marriage and Family Therapy Education-accredited programs. We used thematic analysis to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Coding in thematic analysis can be inductive or deductive, and theme development can be semantic or latent (Braun & Clarke, ). In the current study, we employed an inductive and latent approach, generating our themes “from the bottom up.” An inductive approach is a process of coding in which the data are not fitted into preconceived codes, but the process is instead driven by the data themselves (Piercy et al., ). By interpreting themes on the latent level, we attempted to go beyond explicit description of the data to theorize underlying meanings within them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coding in thematic analysis can be inductive or deductive, and theme development can be semantic or latent (Braun & Clarke, ). In the current study, we employed an inductive and latent approach, generating our themes “from the bottom up.” An inductive approach is a process of coding in which the data are not fitted into preconceived codes, but the process is instead driven by the data themselves (Piercy et al., ). By interpreting themes on the latent level, we attempted to go beyond explicit description of the data to theorize underlying meanings within them.…”
Section: Methodsmentioning
confidence: 99%
“…A six-phase process of thematic analysis (Braun & Clarke, 2006) was used to code participants' responses to the open-ended questions (Piercy et al, 2016). First, the open-response data were entered into MAXQDA (Kuckartz, 2001) and read through multiple times, with initial thoughts and impressions of the data carefully noted.…”
Section: Analysesmentioning
confidence: 99%
“…Assuming that training and supervision are "primary vehicles through which a field evolves" (Liddle, Breunlin, & Schwartz, 1988, p. 4), we hope that our study will contribute to expanding this conversation to the context of training. Along with others (McCandless & Eatough, 2012;Piercy et al, 2016) we believe that research attentive to trainees' voices can enhance our understanding of the complexities and the perplexities of the practice of reflexivity as well as of reflexive processes in training.…”
Section: Resultsmentioning
confidence: 73%
“…Piercy et al. () found that one of the most meaningful experiences for MFT students was how the program connected theory and practice. Furthermore, students found information that was applicable to clinical practice to be particularly helpful.…”
Section: Students’ Experience In Mft Trainingmentioning
confidence: 99%
“…Although scholars have discussed the usefulness of including common factors in training (D'Aniello, 2015;D'Aniello, Alvarado, Hulbert, Izaguirre, & Miller, 2016;Karam, Blow et al, 2015;Karam, Antle, et al, 2015), there is very little research on students' experience with MFT education in general and common factors training specifically. Piercy et al (2016) found that one of the most meaningful experiences for MFT students was how the program connected theory and practice. Furthermore, students found information that was applicable to clinical practice to be particularly helpful.…”
Section: Students' Experience In Mft Trainingmentioning
confidence: 99%